Dakwah Sebagai Kontrol Sosial Masyarakat di Era Perkembangan Zaman - Mubarok, Fadhil; Dyah Ayu Sakawuni; Fahrurrozi Wildanu Faza (CV Omah Kreator, 2024)
Da'wah is an attempt to spread religious teachings, moral values, and religious principles to individuals or communities. While the social aspect includes various aspects of social life, such as culture, politics, economics, and interactions between individuals. In this context, social da'wah refers to efforts to spread religious teachings with a focus on social improvement, community welfare, and meeting social needs. This can include providing assistance to the needy, counseling on religious values in a social context, and various other efforts aimed at improving the social conditions of the community. Da'wah and social aspects are often interrelated, as the delivery of religious messages can also have a positive impact on society. Many religious organizations and charities run social da'wah programs to achieve this goal. However, keep in mind that the implementation of da'wah and social can vary depending on the cultural, religious, and value context that exists in a particular society. Social da'wah is an approach in da'wah that focuses on improving society and social welfare. It involves conveying religious messages as well as taking concrete actions to help people and society. Social da'wah can be carried out through various means, such as education, welfare programs, humanitarian assistance, and efforts to combat social injustice. The goal is to create a better society and get closer to religious values while providing concrete benefits for others.